REVIEW on the monograph "The Caucasian-Caspian region in the policy of the Russian Empire in the first third of the 18th century". / [under the general. ed. Sh.A. Magaramov]. - Makhachkala: IIAE DFITs RAS, 2022. - 322p. - Garunova, Nina Nurmagomedovna (History, Archeology and Ethnography of the Caucasus, 2023)
The collective monograph presents the latest results of the study of the Caspian-Persian vector of the foreign policy of Peter the Great and his successors in the first third of the 18th century. A wide range of historical sources are provided in the book, most of which were collected from the regional and federal archives of Russia, and are introduced into scientific circulation by the authors for the first time. The issues of source study and historiography of the subject are discussed, the features of international relations in the region in connection with the Persian campaign of Peter I are considered, complex issues of the formation and implementation of Russian administrative practice and the integration of the Caspian regions into the imperial system are analyzed, the image of Peter I is reconstructed in the historical memory of the population of Dagestan.
Keywords: Russian empire; Dagestan; emperor; Caspian; army; fortress; Persian campaign; borderlands; commandant